The Complaint's Terms and Methods in Statement of Holy Quran (Journal of the College of Education for Women, 2019)
This research deals with a unique and innovative topic, that is the study of complaint in the Quranic text. Despite its importance, it has never been studied before, because most of the complaint 's meanings in the Quranic text is: the in explicit complaint. The mentioned complaint's expressions in different contexts overlap with other purposes, in particular call method and its peripherals like mourn , ask for help , exclamation and others.Moreover, expressions that reveal complaint are related to the complainant's emotional and psychological status, and the complaint's context.This research deals with the topic into two sections: The first deals with the important expression of complaint such as: iff, ouah, mooing, crying. The second deals with the complaint's methods and contexts .Finally , the study ends with the conclusion.